Precarious work and methodological challenges to study hard-to-reach populations - Rita de Cássia P. Fernandes; Janaína Santos de Siqueira; Matheus F dos Santos; Paulo G. L. Pena; Guilherme L. Werneck; Alex Burdorf (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To describe the methodological challenges and strategies of a web survey on the working conditions and health among delivery workers. METHODS The study population consisted of Brazilian delivery workers operating in the national territory. Procedures include building solid and ongoing collaboration with worker representatives and conducting a four-month data collection from February to May 2022, sharing the link to the online questionnaire on social media such as social networks (Facebook, Instagram) and messaging apps (WhatsApp, Telegram). RESULTS The recruitment of 41 leaders or influencers of delivery workers increased the dissemination of the study, some of whom participated in the consensual validation of the questionnaire; the production of content for social media for the dissemination of the questionnaire link on social networks and applications, and the in-person dissemination of the study at the delivery workers' meeting points during the workday played a fundamental role, totaling around 132 hours in 45 shifts. The strategies adopted for data collection with a hybrid approach to dissemination made it possible to carry out the web survey. After four months of the web survey, 564 delivery workers, 543 men and 18 women, responded to the online questionnaire. CONCLUSION The web survey presented methodological strategies to overcome the challenge of reaching workers, including hybrid work, to increase the participation of workers, on whom epidemiological research is still scarce.